Data Acquisition for Monitoring IoT-Based Hydroponic Automation System Using ESP8266 - Tholib Hariono; Mukhamad Cahyono Putra (NEWTON: Networking and Information Technology, 2021)
Hydroponics is a method of growing crops without using soil, by utilizing water as a solvent for the nutrients that plants need. The role of technology is also needed to help provide nutrition and monitor the state of plants automatically. This study aims to conduct data acquisition on an IOT-based hydroponic plant automation system using ESP8266. Data acquisition is used to monitor temperature data from the DS18B20 sensor, PPM levels from the TDS Meter v1.0 sensor, Ph levels from the Ph Meter v1.1 sensor, water level from TIP 42C, periodic plant growth monitoring based on an image from ESP32 Cam, and as an alternative energy backup using sonar panels on hydroponic plants. Acquired data from each sensor is sent to the Firebase real-time database, every data change is saved to the MySQL server database. The system development method uses the waterfall which includes requirements analysis, system design, implementation, and testing. The results of data acquisition are displayed on the dashboard page in real-time so that they can be easily read by the user. The results of functional and effectiveness testing went well. Monitoring and controlling are done through the website.